Strategi Pengembangan Bank Sampah di Wilayah Depok - Linda Fitrina Hasnam; Rizal Syarief; Ahmad Mukhlis Yusuf (School of Business, Bogor Agricultural University (SB-IPB), 2017)
Waste is a global problem in all countries, including Indonesia, because the accumulation of waste generated is directly proportional to the number of Indonesian population reached 256 million in 2015. The purpose of this study was to identify factors EFE and IFE waste banks in order to survive and sustainable (sustain). Data collection techniques using FGD, expert interviews and questionnaires by WPL Waste Bank customers and their auxiliaries. Data analysis using SWOT and AHP to determine in detail the strategies and priorities for the development activities of the waste bank. The results of the analysis EFE and IFE waste banks shows that this activity is stable and has the potential to grow and develop with consistent with the activities that have taken place, has business planning and development purposes for waste banks, expanding the network of relationships or networking with outsiders and penetration and market development to drive Sales of products of waste processing.Keywords: waste bank, community empowerment, social entrepreneurship, SWOT, AHPAbstrak: Sampah adalah masalah global di semua negara termasuk Indonesia, sebab akumulasi sampah yang dihasilkan berbanding lurus dengan jumlah penduduk Indonesia yang mencapai 256 juta jiwa pada tahun 2015. Tujuan penelitian ini adalah untuk mengidentifikasi faktor EFE dan IFE bank sampah agar dapat bertahan serta berkelanjutan (sustain). Teknik pengumpulan data menggunakan FGD, wawancara pakar dan pengisian kuesioner oleh nasabah Bank Sampah WPL dan binaannya. Analisis data menggunakan metode SWOT dan AHP untuk menentukan strategi secara detail dan prioritas utama pengembangan kegiatan bank sampah. Hasil analisis EFE dan IFE bank sampah menunjukkan bahwa kegiatan ini berpotensi untuk tumbuh dan berkembang dengan tetap konsisten melakukan kegiatan yang telah berlangsung, memiliki perencanaan bisnis dan tujuan pengembangan bank sampah, memperluas jaringan hubungan atau networking dengan pihak luar serta melakukan penetrasi dan pengembangan pasar untuk mendorong penjualan produk hasil pengolahan sampah.Kata kunci: bank sampah, pemberdayaan masyarakat, kewirausahaan sosial, SWOT, AHP